2019
DOI: 10.3390/rs11020111
|View full text |Cite
|
Sign up to set email alerts
|

Yield Estimation of Paddy Rice Based on Satellite Imagery: Comparison of Global and Local Regression Models

Abstract: Precisely estimating the yield of paddy rice is crucial for national food security and development evaluation. Rice yield estimation based on satellite imagery is usually performed with global regression models; however, estimation errors may occur because the spatial variation is not considered. Therefore, this study proposed an approach estimating paddy rice yield based on global and local regression models. In our study area, the overall per-field data might not available because it took lots of time and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 73 publications
1
29
0
Order By: Relevance
“…Gong et al [ 24 ] found that NDVI is of great help to the prediction of rapeseed yield using unmanned aerial vehicle (UAV) imagery. Moreover, VI also contributes significantly to yield estimation for crops such as rice [ 25 , 26 ], maize [ 27 , 28 ], and wheat [ 29 , 30 ]. The simulation results of crop characteristic parameters can be obtained by constructing the linear or nonlinear empirical relationship [ 31 ] or by machine learning methods [ 32 ] like support vector machine (SVM), random forest (RF), partial least squares (PLS) and artificial neural network (ANN) between VIs and these parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Gong et al [ 24 ] found that NDVI is of great help to the prediction of rapeseed yield using unmanned aerial vehicle (UAV) imagery. Moreover, VI also contributes significantly to yield estimation for crops such as rice [ 25 , 26 ], maize [ 27 , 28 ], and wheat [ 29 , 30 ]. The simulation results of crop characteristic parameters can be obtained by constructing the linear or nonlinear empirical relationship [ 31 ] or by machine learning methods [ 32 ] like support vector machine (SVM), random forest (RF), partial least squares (PLS) and artificial neural network (ANN) between VIs and these parameters.…”
Section: Introductionmentioning
confidence: 99%
“…A study in [38] concluded that soil quality is important in predicting the productivity of crops, which would lead to provide complementary information and improve the accuracy of yield prediction. Remote sensing will help to cover a vast scale with non-invasive and efficient techniques to detect the spatial variability in plant status with high temporal resolution [39]. There is a large implementation of remote sensing approaches based on infrared VOLUME 4, 2016 This work is licensed under a Creative Commons Attribution 4.0 License.…”
Section: A Popular Features Used In Crop Yield Predictionmentioning
confidence: 99%
“…Shiu and Chuang [17], in their paper entitled "Yield Estimation of Paddy Rice Based on Satellite Imagery: Comparison of Global and Local Regression Models", proposed an efficient approach to estimate paddy rice yield using (1) the global regression models including the ordinary least squares (OLS) and support vector regression (SVR) and (2) the local model of geographically weighted regression (GWR).…”
Section: Remote Sensing Technology and Its Applicationsmentioning
confidence: 99%